The PTPIP51 coiled-coil domain is important in VAPB binding, formation of ER-mitochondria contacts and IP3 receptor delivery of Ca2+ to mitochondria - Mórotz, Gábor M.; Martín-Guerrero, Sandra M.; Markovinovic, Andrea; Paillusson, Sebastien; Russell, Matthew R. G.; Machado, Pedro M. Pereira; Fleck, Roland A.; Noble, Wendy; Miller, Christopher C.J. (Frontiers in Cell and Developmental Biology, 2022)
Signaling between the endoplasmic reticulum (ER) and mitochondria regulates a number of fundamental physiological processes. This signaling involves close physical contacts between the two organelles that are mediated by the VAPB-PTPIP51 "tethering" proteins. The VAPB-PTPIP51 tethers facilitate inositol 1,4,5-trisphosphate (IP3) receptor delivery of Ca2+ from ER to mitochondria and damage to the tethers is seen in Alzheimer's disease, Parkinson's disease and frontotemporal dementia with related amyotrophic lateral sclerosis (FTD/ALS). Understanding the mechanisms that regulate the VAPB-PTPIP51 interaction thus represents an important area of research. Recent studies suggest that an FFAT motif in PTPIP51 is key to its binding to VAPB but this work relies on in vitro studies with short peptides. Cellular studies to support this notion with full-length proteins are lacking. Here we address this issue. Immunoprecipitation assays from transfected cells revealed that deletion of the PTPIP51 FFAT motif has little effect on VAPB binding. However, mutation and deletion of a nearby coiled-coil domain markedly affects this binding. Using electron microscopy, we then show that deletion of the coiled-coil domain but not FFAT motif abrogates the effect of PTPIP51 on ER-mitochondria contacts. Finally, we show that deletion of the coiled-coil domain but not FFAT motif abrogates the effect of PTPIP51 on IP3 receptor mediated delivery of Ca2+ to mitochondria. Thus, the coiled-coil domain is essential for PTPIP51 ER-mitochondria signaling functions.